2014
DOI: 10.1093/jnci/dju182
|View full text |Cite
|
Sign up to set email alerts
|

Role of BRAFV600E in the First Preclinical Model of Multifocal Infiltrating Myopericytoma Development and Microenvironment

Abstract: Myopericytoma (MPC) is a rare tumor with perivascular proliferation of pluripotent stem-cell-like pericytes. Although indolent, MPC may be locally aggressive with recurrent disease. The pathogenesis and diagnostic biomarkers of MPC are poorly understood. We discovered that 15% of benign MPCs (thyroid, skin; 3 of 20 samples) harbored BRAF(WT/V600E); 33.3% (1 of 3 samples) of BRAF(WT/V600E)-MPCs were multifocal/infiltrative/recurrent. Patient-MPC and primary MPC cells harbored BRAF(WT/V600E), were clonal and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Myopericytoma shows variable cellularity and a collagenous or sometimes myxoid stroma, and may also show bulging subendothelial proliferation of tumor cells within vessels walls. Consistent genetic alterations have not been identified in myopericytoma, apart from a unique variant characterized by translocation t(7; 12)(p22; q13) which results in ACTB-GLI1 fusion [30][31][32] and a report of BRAF V600E mutations in a subset of myopericytomas [33]. Similar to a prior report [34], nuclear b-catenin expression is consistently absent in myofibroma and is useful in the distinction between sinonasal HPC and myopericytoma.…”
Section: Discussionmentioning
confidence: 54%
“…Myopericytoma shows variable cellularity and a collagenous or sometimes myxoid stroma, and may also show bulging subendothelial proliferation of tumor cells within vessels walls. Consistent genetic alterations have not been identified in myopericytoma, apart from a unique variant characterized by translocation t(7; 12)(p22; q13) which results in ACTB-GLI1 fusion [30][31][32] and a report of BRAF V600E mutations in a subset of myopericytomas [33]. Similar to a prior report [34], nuclear b-catenin expression is consistently absent in myofibroma and is useful in the distinction between sinonasal HPC and myopericytoma.…”
Section: Discussionmentioning
confidence: 54%
“…In vitro and in vivo studies showed significant effects of BRAF V600E mutation on the tumor microenvironment promoting invasiveness and angiogenesis. These effects were reversible by the specific anti BRAF inhibitor, Vemurafenib, in tumors harbouring BRAF V600E mutation but not in the WT BRAF tumors (Sadow et al 2014). This suggests that cells other than the epithelial follicular cells from which TC normally arises might harbour mutations that contribute to the progression of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting results might also reflect the role of tumor microenvironment. Recent studies have shown a role for BRAF V600E mutation in thyroid tumors that are mesenchymal in origin (Sadow et al 2014). Sadow et al reported the presence of BRAF V600E mutation in three benign myopericytomas, a rare frequently benign mesenchymal tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, BRAF V600E mutation can cause constitutive activation of the MAPK signaling pathway. BRAF V600E also plays a role in the cellular microenvironment of cancer [13,14]. Thus, the MAPK pathway and its mutated BRAF can be used as therapeutic targets of TC.…”
Section: Introductionmentioning
confidence: 99%